2015
DOI: 10.1007/s12010-015-1631-1
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of a Cysteine-Rich 14-kDa Antibacterial Peptide from the Granular Hemocytes of Mangrove Crab Episesarma tetragonum and Its Antibiofilm Activity

Abstract: Antimicrobial peptide (AMP) crustin is a type of immune molecule present in the immune system of crustaceans and response against microbial invasion. In the present study, we have identified and characterized the cationic, amphipathic structure consisting of AMP crustin from a mangrove crab Episesarma tetragonum using CM Sepharose-based cation exchange column chromatography. E. tetragonum crustin showed a single band of 14 kDa on SDS-PAGE and the homogeneity showed retention time of 8.4 min in RP-HPLC. Functio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 49 publications
1
3
0
Order By: Relevance
“…Haemocyanin exhibited affinity towards bacteria resulting in elimination of the microbial pathogen directly from the internal environment of the potential crustacean host. Our results get supported by Sivakamavalli et al (2015) reporting that the haemocyanin affinity towards bacteria was noticed in M. japonicus haemocyanin, which was able to agglutinate both Gram-positive and Gram-negative bacteria. Due to more prevalence on antibiotic resistance in Gram-negative bacteria, the Pp-Hc antibiofilm activity was checked against them, i.e., V. alginolyticus, V. harveyi, V. parahaemolyticus, P. aeruginosa and P. vulgaris.…”
Section: Discussionsupporting
confidence: 87%
“…Haemocyanin exhibited affinity towards bacteria resulting in elimination of the microbial pathogen directly from the internal environment of the potential crustacean host. Our results get supported by Sivakamavalli et al (2015) reporting that the haemocyanin affinity towards bacteria was noticed in M. japonicus haemocyanin, which was able to agglutinate both Gram-positive and Gram-negative bacteria. Due to more prevalence on antibiotic resistance in Gram-negative bacteria, the Pp-Hc antibiofilm activity was checked against them, i.e., V. alginolyticus, V. harveyi, V. parahaemolyticus, P. aeruginosa and P. vulgaris.…”
Section: Discussionsupporting
confidence: 87%
“…MmLec therefore has a great potential to inhibit and accumulate undesirable pathogenic products by preventing the proliferation and colonization as well as interrupting their biofilm architectural cascade. Jayanthi et al [50], Sivakamavalli et al [71] and Anjugam et al [72] have also reported the similar activities of various lectins purified from other shrimp species. They also postulated that lectins, showing antibiofilm properties can be treated as a potent antimicrobial therapeutic tool.…”
Section: Discussionmentioning
confidence: 83%
“… 71 Specially, crustin from crustaceans and plant HDPs are rich in cysteines ( Table 1 ). 111 , 112 These amino acids and features mentioned above are often used while designing AMPs.…”
Section: General Characteristics Of Ampsmentioning
confidence: 99%